RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA ILEGAL FISIHING YANG DILAKUKAN NELAYAN INDONESIA - RAMEZ (ALWAQFU: Jurnal Hukum Ekonomi dan Wakaf, 2024)
Illegal fishing is a term used and/or attached to perpetrators of fishing crimes in sea waters by fishermen. Where the fishing practices carried out by these fishermen do not comply with applicable legal regulations. Specifically in this research, the fishermen who catch the fish in question are Indonesian fishermen who violate the law in fishing activities in Indonesian sea waters. The types and forms of violations committed by these fishermen vary, such as: not completing a fishing permit, using prohibited fishing gear, to the actions of fishermen who damage the marine environment and threaten the marine biota around them. The Indonesian government has made various efforts to combat the behavior of fishermen who violate legal regulations regarding illegal fishing. Starting from coaching and legal counseling to fishermen, carrying out restorative justice. This type of research uses a normative juridical approach and uses qualitative analysis techniques which are then explained and analyzed using descriptive analytical methods. The type of approach used in writing this thesis is the library research approach, namely by studying books and documents related to the topic of the article and also using the statutory regulatory approach, namely by reviewing existing statutory regulations. related to the topic discussed in this research. The results of the research and discussion in this study reveal that this type of illegal fishing crime has been occurring for a long time and repeatedly among Indonesian fishermen. There are fishermen who commit these crimes deliberately, but many fishermen do not know anything about the fishing regulations that apply in Indonesia, this is due to a lack of legal outreach to the fishing community who are unfamiliar with the law itself. For these ordinary fishermen, the government applies restorative justice to them. Where the legal settlement applied is based on a firm warning not to repeat violations of fishing laws and requires them to complete fishing requirements in accordance with applicable legal regulations. However, for fishermen who already know but still violate the law, the government, through the legal apparatus tasked with supervising and protecting Indonesia's maritime affairs, applies sanctions and legal traps appropriate to their actions, namely prison and fines according to the type and nature of their actions. a form of illegal fishing crime that he committed.